Ben Shahn's New Deal Murals : Jewish Identity in the American Scene - Linden, Diana L. (Book collections on Project MUSE., 2015)
"Lithuanian-born artist Ben Shahn learned fresco painting as an assistant to Diego Rivera in the 1930s and created his own visually powerful, technically sophisticated, and stylistically innovative artworks as part of the New Deal Arts Project's national mural program. In Ben Shahn's New Deal Murals: Jewish Identity in the American Scene author Diana L. Linden demonstrates that Shahn mined his Jewish heritage and left-leaning politics for his style and subject matter, offering insight into his murals' creation and their sometimes complicated reception by officials, the public, and the press."--Publisher's website.